WHO European Childhood Obesity Surveillance Initiative: health-risk behaviours on nutrition and physical activity in 6-9-year-old schoolchildren - Wijnhoven, Trudy M A; van Raaij, Joop M A; Yngve, Agneta; Sjöberg, Agneta; Kunešová, Marie; Duleva, Vesselka; Petrauskiene, Ausra; Rito, Ana I; Breda, João (Public health nutrition, 2015)
OBJECTIVE: To assess to what extent eight behavioural health risks related to breakfast and food consumption and five behavioural health risks related to physical activity, screen time and sleep duration are present among schoolchildren, and to examine whether health-risk behaviours are associated with obesity. DESIGN: Cross-sectional design as part of the WHO European Childhood Obesity Surveillance Initiative (school year 2007/2008). Children's behavioural data were reported by their parents and children's weight and height measured by trained fieldworkers. Descriptive statistics and logistic regression analyses were performed. SETTING: Primary schools in Bulgaria, Lithuania, Portugal and Sweden; paediatric clinics in the Czech Republic. SUBJECTS: Nationally representative samples of 6-9-year-olds (n 15 643). RESULTS: All thirteen risk behaviours differed statistically significantly across countries. Highest prevalence estimates of risk behaviours were observed in Bulgaria and lowest in Sweden. Not having breakfast daily and spending screen time ≥2 h/d were clearly positively associated with obesity. The same was true for eating 'foods like pizza, French fries, hamburgers, sausages or meat pies' >3 d/week and playing outside <1 h/d. Surprisingly, other individual unhealthy eating or less favourable physical activity behaviours showed either no or significant negative associations with obesity. A combination of multiple less favourable physical activity behaviours showed positive associations with obesity, whereas multiple unhealthy eating behaviours combined did not lead to higher odds of obesity. CONCLUSIONS: Despite a categorization based on international health recommendations, individual associations of the thirteen health-risk behaviours with obesity were not consistent, whereas presence of multiple physical activity-related risk behaviours was clearly associated with higher odds of obesity.
Keywords: index tělesné hmotnosti; Parents; Cross-Sectional Studies; Prevalence; dieta; pohybová aktivita; chování dětí; sedavý životní styl; Obesity; Europe; Sedentary Behavior; Food consumption; Evropa; podpora zdraví; adherence pacienta; mužské pohlaví; prevalence; Světová zdravotnická organizace; Physical activity; Health Promotion; průřezové studie; Pediatric Obesity; World Health Organization; fyziologie výživy dětí; Body Mass Index; dítě; Child; výživa - přehledy; ženské pohlaví; Humans; snídaně; Nutrition Surveys; epidemiologické monitorování; Child Nutritional Physiological Phenomena; Patient Compliance; Child Behavior; Schoolchildren; Risk; riziko; Breakfast; Diet; Motor Activity; Epidemiological Monitoring; Female; obezita dětí a dospívajících; rodiče; lidé; Male